A learning agenda to build the evidence base for strengthening global health information systems. Issue 2 (May 2022) - Reynolds, Heidi W; Salentine, Shannon; Silvestre, Eva; Millar, Elizabeth; Strahley, Ashley; Cannon, Abby C; Bobrow, Emily A
Background: Evidence-based interventions are necessary for planning and investing in health information systems (HIS) and for strengthening those systems to collect, manage, sort and analyse health data to support informed decision-making. However, evidence and guidance on HIS strengthening in low- and middle-income countries have been historically lacking. Objective: This article describes the approach, methods, lessons learned and recommendations from 5 years of applying our learning agenda to strengthen the evidence base for effective HIS interventions. Methods: The first step was to define key questions about characteristics, stages of progression, and factors and conditions of HIS performance progress. We established a team and larger advisory group to guide the implementation of activities to build the evidence base to answer questions. We strengthened learning networks to share information. Results: The process of applying the learning agenda provided a unique opportunity to learn by doing, strategically collecting information about monitoring and evaluating HIS strengthening interventions and building a body of evidence. There are now models and tools to strengthen HIS, improved indicators and measures, country HIS profiles, documentation of interventions, a searchable database of HIS assessment tools and evidence generated through syntheses and evaluation results. Conclusion: The systematic application of learning agenda processes and activities resulted in increased evidence, information, guidance and tools for HIS strengthening and a resource centre, making that information accessible and available globally. Implications: We describe the inputs, processes and lessons learned, so that others interested in designing a successful learning agenda have access to evidence of how to do so.